2014
DOI: 10.5796/electrochemistry.82.654
|View full text |Cite
|
Sign up to set email alerts
|

Microbubble Formation from Ionic Vacancies in Copper Electrodeposition under a High Magnetic Field

Abstract: Ionic vacancies created in copper electrodeposition have been first observed by converting to microbubbles via. nanobubbles. Since the copper deposition potential was much more positive than hydrogen evolution one, the microbubbles were ascribed not to hydrogen bubbles but to the ionic vacancies. Then, the evolution times of the microbubbles at an overpotential of −300 mV were examined under various magnetic flux densities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 8 publications
1
19
0
Order By: Relevance
“…In copper deposition, the same kind of microbubble evolution has been also observed, 12 where the measurement of the partial molar volume of ionic vacancy revealed that ionic vacancies are stoichiometrically created with electrode reactions. These experimental results suggest that evolution of ionic vacancy is a universal phenomenon in electrode reactions, and that ionic vacancies emerge with the conservation of momentum as well as electric charge; if ionic vacancy is created in anodic copper dissolution, as shown in Eqs.…”
mentioning
confidence: 75%
See 3 more Smart Citations
“…In copper deposition, the same kind of microbubble evolution has been also observed, 12 where the measurement of the partial molar volume of ionic vacancy revealed that ionic vacancies are stoichiometrically created with electrode reactions. These experimental results suggest that evolution of ionic vacancy is a universal phenomenon in electrode reactions, and that ionic vacancies emerge with the conservation of momentum as well as electric charge; if ionic vacancy is created in anodic copper dissolution, as shown in Eqs.…”
mentioning
confidence: 75%
“…The validity of these electrodes has been proved by the preceding experiments. 11,12 Then, the microbubbles are in situ observed by optical microscope. To ensure the process mentioned above, the origin of the gas contained in the microbubbles is examined by the following blank Electrochemistry, 83 (7), 549-553 (2015) test; prior to experiment, all the gases including dissolved gases are removed from the electrode cell with vacuum pump, which makes nanobubble formation impossible and will prepare the electrode surface without microbubble evolution.…”
Section: Theoreticalmentioning
confidence: 99%
See 2 more Smart Citations
“…The existence of such vacancies was confirmed by the observation of micro-bubbles arising from the aggregation of ionic vacancies. 31 In the vicinity of electrodes, the ionic vacancies extremely decrease the viscosity and the friction, 20 leading to the excitation of nanometer-scale MHD vortices. Consequently, the most probable chiral site on the MED film surfaces is a screw dislocation.…”
Section: ¹2mentioning
confidence: 99%